Penyuluhan Status Harta Waris Islam Terhadap Anak Angkat kepada Seluruh Civitas Universitas Sains Islam Malaysia - Muhammad Irkham Firdaus; Mohammad Ghozali; Jaya Sahputra (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2024)
This Community Service (PKM) focuses on providing counseling about the legal status of adopted children's inheritance rights from their adoptive parents. An adopted child is a child whose rights have been transferred from the family environment and authority of the biological parents, legal guardians, or other persons responsible for caring for, educating and raising the child. The legal status of adopted children in the perspective of laws in Indonesia and Malaysia is legal, however it then becomes an issue when faced with their rights within the inheritance assets of their adoptive parents. In Islamic inheritance law, adopted children do not have legal power over inheritance rights from their adoptive parents, except through obligatory wills (wasiat wajibah). Meanwhile, in positive law, adopted children obtain equal status as biological children, so that adopted children can become heirs. This PKM program is carried out for all USIM civitas (lecturers, staff, employees, workers) in collaboration with the USIM Faroid Study Center. This PKM program aims to provide an understanding of the inheritance rights status of adopted children. This PKM program uses socialization, counseling, and mentoring methods.